PERAN USER GENERATED CONTENT (UGC) INSTAGRAM PADA INDUSTRI MAKANAN - Desi Rubyanti; Irwansyah Irwansyah (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
Participatory web era allows more social media users’ contribution to virtual communities, including creating User-Generated Content (UGC) for information sharing and communicating with other users. Awareness and informing concepts are brought by UGC content through discussion and/or posts can. In the food industry, UGC can act as Electronic-Word of Mouth with contributions and creations which are produced by users. Information about the function of organic information. Food industry players such as the Indomie brand see the opportunity to use UGC as an initial step for Electronic Word of Mouth in achieving its audience awareness goals. Using the phenomenological method, this qualitative study conducted data mining through informants who were directly involved in the UGC-based campaign on Indomie HypeAbis Chitato Taste of Roast Beef. Data shows sending trial products can build E-WOM organically and elevate share of voice through UGC that produced by Indomielovers. Strong UGC also needs to be supported by strong branding and motivation from users' prestige towards food trends to get recognition in the virtual community.